Wednesday

April 16, 2014

April 16, 2014

Posted by **John** on Friday, March 28, 2008 at 6:52pm.

f(x)=2x^5+2x^3

f^-1x=2(-x)^5+2(-x)^3

f^-1x=-2x^5+-2x^3

f^-1x=-2x^5-2x^3

f(x)=2x^5+2x^3

f^-1x=2(-x)^5+2(-x)^3

f^-1x=-2x^5+2(-x)^3

f^-1x=(-2x^5)+(-2x^3)

f^-1x=-2x^5-2x^3

Not even. This function is odd.

- Algebra -
**Damon**, Friday, March 28, 2008 at 6:58pmthat is f(-x) you want but your answer is correct.

f(-x) = 2(-x)^5 + 2(-x)^3

but (-x)^5 = - x^5

and (-x)^3 = - x^3

so

f(-x) = -2 x^5 - 2 x^3

= -f(x)

so odd because f(-x) = - f(x))

**Related Questions**

Algebra2 - Check? Give the slope and y-intercept of the given line. 1. 2x-3y=6...

Algebra2 - Check? Give the slope and y-intercept of the given line. 1. 2x-3y=6...

Algebra - Here is what I am trying to factor: 2x^2 + 3x + 1 = 0. I split the ...

Intermediate Algebra - Solve using the substitution method. Show your work. If ...

ALgebra - I am supposed to preform the indicated divisons: 8x^3-6x^2+2x divided ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

math,correction - can someone correct this for me. 7(x –3) > 5x - 14 7x –21 &...

Intermediate Algebra Solve - x + 1 / x = 3/2 x + 1(2) = 3x 2x + 2 = 3x -2x -2x ...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...